Effect of Post-hatch Feeding on Broiler Performance - Saki, A.A. (International Journal of Poultry Science, 2004)
Broiler performance in the end of rearing period may be influenced by post-hatch feeding. Four hundreds and eighty Arian day-old chicken was placed in 4 treatments with four replications and 30 chicken in each. This experiment was arranged in complete random design (CRD). Twelve hours fasting, corn feeding, starter feeding and 24 hour fasting were used as a treatments. No significant differences (P>0.05) were observed in feed intake and feed conversion ratio in 7, 14, 21, 35 and 42 day old chicken. The organelles (legs, wings, back, breast meat, Abdominal fat, full intestinal, gizzard and neck) had shown similar reaction. Body weight increased significantly (P